Whistle-Blowing: Target Firm Characteristics and Economic Consequences - Bowen, Robert M.; Call, Andrew C.; Rajgopal, Shiva (The Accounting Review, 2010)
ABSTRACT: We document the first systematic evidence on the characteristics and economic consequences of firms subject to employee allegations of corporate financial misdeeds. First, compared to a control group that avoided public whistle-blowing allegations, firms subject to whistle-blowing allegations were characterized by unique firm-specific factors that led employees to expose alleged financial misdeeds. Second, on average, whistle-blowing announcements were associated with a negative 2.8 percent market-adjusted five-day stock price reaction; this reaction was especially negative for allegations involving earnings management (−7.3 percent). Third, compared to a control group that exhibits similar characteristics, firms subject to whistle-blowing allegations were associated with further negative consequences including earnings restatements, shareholder lawsuits, and negative future operating and stock return performance. Finally, whistle-blowing targets exposed by the press were more likely to make subsequent improvements in corporate governance. Our results suggest whistle-blowing is far from a trivial nuisance for targeted firms, and on average, appears to be a useful mechanism for uncovering agency issues.